Ti site occupancy in zircon - Tailby, N.; Walker, A.; Berry, A.; Hermann, J.; Evans, Katy; Mavrogenes, J.; O'Neil, H.; Rodina, I.; Soldatov, A.; Rubatto, D.; Sutton, S. (Pergamon-Elsevier Science Ltd, 2011)
Ti site occupancy in zircon (ZrSiO4) is fundamental to thermobarometry because substitution mechanisms control Ti content–temperature relations. Here we describe the results of three independent methods used to demonstrate that Ti substitutes for Si and not Zr in zircon. Zircon grains were synthesized from oxide powders held in a Na2WO4 flux at 1 bar and 1300 °C. Zircon grains equilibrated with rutile + cristobalite show Ti contents (1201 ppm) nearly half that of zircon grains equilibrated with srilankite ((Ti,Zr)O2) + tetragonal zirconia (2640 ppm). The lower Ti content of zircon grains produced at silica-saturated conditions indicates that Ti substitution predominately occurs on the Si site. Moreover, the higher Ti contents of silica-saturated experiments at 1 bar (1201 ppm), relative to those at 1 GPa (457 ppm, Ferry and Watson, 2007), indicates a substantial pressure effect on Ti solubility in zircon. Measured Ti K-a edge X-ray Absorption Near Edge Structure (XANES) spectra of synthetic zircon grains show energies and normalized intensities akin to those seen among tetrahedrally coordinated Ti-bearing standard minerals, strongly suggesting that Ti occupies the Si site. Density functional theory (DFT) calculations confirm that Ti substitution is most likely to occur on the Si site and predict a Ti–O bond length of 1.797 Å (compared to an average of 2.160 Å for substitution on the Zr site), in excellent agreement with X-ray Absorption Fine Structure (EXAFS) spectra of experimentally grown zircon grains which indicate a value of 1.76(1) Å.The software FEFF 8.4 was used to simulate XANES spectra from the defect structures determined by DFT for Ti substituting on both the Si and Zr sites. The predicted spectrum for Ti on the Si site reproduces all the key features of the experimental zircon spectra, whereas Ti on the Zr site is markedly different. All applied methods confirm that Ti substitutes for Si in zircon. Consequently, the Ti content of zircon at a given pressure is not only a function of temperature, but will increase with decreasing silica activity. Because elements that activate or quench cathodoluminescence (CL) in zircon are incorporated into the Zr site, a decoupling of CL from Ti contents – incorporated on the Si site in zircon is expected. This hypothesis has been verified by a systematic CL-trace element study of natural and experimental zircon.